2020
DOI: 10.1038/s41598-020-59527-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Anthropometric Characteristics and Breast Cancer Incidence in the Daughter

Abstract: the intrauterine and early life environments have been linked to the etiology of breast cancer in prior studies. We prospectively examined whether maternal and newborn anthropometric factors as reported by the mother are related to an increased incidence of adult breast cancer in the daughter. We used data from 35,133 mother-daughter dyads of the Nurses' Health Study (NHS) II and the Nurses' Mothers' Cohort Study. In 2001, living mothers of NHS II participants who were free of cancer completed a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Based on a review of the full texts of 112 studies, 90 studies were excluded, mainly because they were reviews, nondescendant cancers, lack of information on maternal BMI or GWG, unclear or incomplete data, or duplicated data. Finally, twenty-two studies were identified as eligible and included in the present meta-analysis ( Figure 1 ) [ 13 , 14 , 15 , 16 , 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a review of the full texts of 112 studies, 90 studies were excluded, mainly because they were reviews, nondescendant cancers, lack of information on maternal BMI or GWG, unclear or incomplete data, or duplicated data. Finally, twenty-two studies were identified as eligible and included in the present meta-analysis ( Figure 1 ) [ 13 , 14 , 15 , 16 , 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the association between maternal BMI and the risk of total cancer in offspring [ 13 , 14 , 15 , 16 , 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 ]. …”
Section: Figurementioning
confidence: 99%
“…Thirdly, the population-based nature of the sample increases the heterogeneity of the study population. In addition, almost none of the previous studies have adjusted antenatal anthropometrics with plurality and gestational age, although some have used the Ponderal Index (kg/m 3 ) (3,4,6).…”
Section: Discussionmentioning
confidence: 99%
“…The number of menstrual cycles during a woman's lifetime (age of menarche, age of first pregnancy, parity and onset of natural menopause) is strongly connected to higher risk of both premenopausal and postmenopausal breast cancer (1,2). Of the early factors, some studies have shown a positive connection between birth length (3)(4)(5)(6)(7) and birth weight (3,6,7) and risk of breast cancer. The connection between birth weight and risk of breast cancer has been found particularly among premenopausal women (8,9) but this has not been observed in all studies (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results of many studies suggest that birth parameters as a surrogate for cumulative exposure in utero are associated with cancer risk in adulthood 3 . In this context, an increasing number of studies have converged on the relationship between birth weight and subsequent breast cancer risk 4-8 . Most of the studies have compared the outcomes between low birth weight, high birth weight, and normal birth weight; however, the conclusions have not been consistent due to differences in grouping criteria across studies.…”
mentioning
confidence: 99%